2005
DOI: 10.1111/j.1600-0668.2005.00365.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction potential of urban PM2.5 mortality risk using modern ventilation systems in buildings

Abstract: It has been suggested that indoor concentrations of ambient particles and the associated health risks can be reduced by using mechanical ventilation systems with supply air filtering in buildings. The current work quantifies the effects of these concentration reductions on population exposures using population-based data from Helsinki and an exposure model. The estimated exposure reductions suggest that correctly defined building codes may reduce annual premature mortality by hundreds in Finland and by tens of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 31 publications
1
53
0
Order By: Relevance
“…This is consistent with other literature, which identifies microenvironments such as food courts as well as cooking activities as important sources of exposure to these pollutants (Chang et al, 2000;Levy et al, 2002). It is well documented in a variety of settings that reduced exposures to ambient source particulate matter are observed indoors (Wilson, Mage and Grant, 2000;Hanninen et al, 2005;Wallace and Williams, 2005). The health significance of these changes in exposure, that is, the relative toxicity of outdoor vs. indoor source particulate matter, remains to be evaluated.…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with other literature, which identifies microenvironments such as food courts as well as cooking activities as important sources of exposure to these pollutants (Chang et al, 2000;Levy et al, 2002). It is well documented in a variety of settings that reduced exposures to ambient source particulate matter are observed indoors (Wilson, Mage and Grant, 2000;Hanninen et al, 2005;Wallace and Williams, 2005). The health significance of these changes in exposure, that is, the relative toxicity of outdoor vs. indoor source particulate matter, remains to be evaluated.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have demonstrated correlations between F inf and a number of building, meteorological and behavioral factors; however, such studies do not use data readily available for large populations. Factors found to be related to F inf include housing variables such as age, size, value, square footage, and ventilation conditions (Wallace, 1996;Sherman and Dickerhoff, 1998;Ozkaynak et al, 1999;Ebelt et al, 2000;Sherman and Matson, 2001;Thornburg et al, 2001;McKone et al, 2002;Hanninen et al, 2005;Chan et al, 2005); meteorological factors including temperature and exposure to wind and precipitation (Sherman and Dickerhoff, 1998;Chao and Tung, 2001;McKone et al, 2002); and occupant behaviors and characteristics, such as occupant income, window opening, and use of air conditioners and air filters (Sherman and Dickerhoff, 1998;Mosley et al, 2001;Janssen et al, 2002;Wallace et al, 2003;Koenig et al, 2005). A study by Chan et al (2005) analyzed approximately 70,000 air leakage measurements (a parameter related to F inf ) in the United State to determine predictive housing characteristics and found year of construction, size of dwelling and whether the dwelling was either energy-efficient or occupied by a low-income family to be important predictors of normalized leakage.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency, removal rates, and other performance characteristics of some of these devices have been characterized empirically (Chen et al, 2006;Shaughnessy and Sextro, 2006;MacIntosh et al, 2008). The potential for advanced filtration technology to mitigate indoor exposure to PM 2.5 of ambient origin in Europe was estimated from results of the EXPOLIS study (Hanninen et al, 2005). A similar modeling analysis was conducted for buildings in Singapore (Sultan, 2007).…”
Section: Introductionmentioning
confidence: 99%